Change of lipid peroxidation and antioxidant system at the development of experimental peritonitis - Yu. A. Ermola (Patologìâ)
The article is devoted to the analysis of lipid peroxidation and antioxidant system of blood serum during the experimental peritonitis of varying severity. It was revealed that the activation of free radical oxidation during the experimental peritonitis depends on the severity of its course and may appear to be one of the major mechanisms associated with the formation of the system changes during the pathology development. peritonitis; lipid peroxidation; antioxidant system; inflammation